Prediction of Erosion Using The USLE Method in Community Oil Palm Plantations in Kualuh Selatan District, North Labuhanbatu - Fitra Syawa Harahap; Walida Hilwa; Abdul Rauf; Rahmanta Rahmanta; Arman Harahap; Harahap Sulaiman; Sudarijah; Siarudin Mohamad; Syafii Syafrudin; Rizwan Muhammad; Gunawan Indra (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
The process of erosion leads to the loss of fertile topsoil and a reduction in the soil's capacity to store and absorb water. At the research site, community oil palm plantations in Tanjung Pasir Village, Kualuh Selatan District, North Labuhanbatu Regency, land clearing was conducted through logging, and in some cases, burning. Subsequent plantation management was carried out without implementing soil conservation measures and while disregarding environmental factors, resulting in soil degradation and productivity decline linked to erosion. This study aims to predict the magnitude of erosion using the Universal Soil Loss Equation (USLE) method, calculate the tolerable soil loss, and analyze the erosion hazard level. The USLE method was applied by calculating the causative factors of erosion: rainfall erosivity (R), soil erodibility (K), slope length and steepness (LS), cover management (C), and conservation practices (P). The predicted erosion values were then compared to the tolerable soil loss values to determine the necessity of conservation interventions. The results indicate that the highest predicted erosion value (A) was 521.73 tons/ha/year on plot KS1, while the lowest was 111.09 tons/ha/year on plot KS5. Meanwhile, the tolerable soil loss (TSL) ranged from 43.86 to 64.38 tons/ha/year. Based on this comparison, two classes of erosion hazard were identified: very high and high. Both classes exhibited predicted erosion values far exceeding the permissible limits. Therefore, conservation measures are imperative, one of which involves planting dense Legume Cover Crops (LCC).